IMPROVEMENT OF KNOWLEDGE ABOUT CIGARETTE THROUGH HEALTH CARE ABOUT HEALTHY BEHAVIOR BY AVOIDING CIGARETTE - Elok Triestuning; Herlins Gretsia Oratmangun; Amilia Mega Asma; Cholilul Rochman; Defi Silahturrohmi Nisaul Khoiro; Khoirotun Niswah; Ria Valy Oratmangun (Community Service Journal of Indonesia, 2020)
Health promotion activities on Healthy Living Behavior by Avoiding Smoking in Al Islam Middle School, Sidoarjo is one form of community service in the form of counseling aimed at increasing children's knowledge about how to avoid smoking for both active smokers and passive smokers. The activity was carried out on November 29, 2019 at the Al Islam Middle School, Sidoarjo. The target is grade IX students of Al Islam Middle School, Sidoarjo. Before the activity is carried out, there is a process of compiling the activity for approximately 3 weeks before the activity is carried out, starting from determining the theme of counseling to submitting permits to the parties concerned. As a form of evaluation, the activity was attended by 30 students of class IX, participants took part in the activity happily and looked very enthusiastic, health promotion activities could run on time and smoothly. Keywords: Knowledge, health care, health behavior, avoiding cigarette.